A generalized solution for transient temperature distribution in an internally/ externally insulated cylindrical shell - Samria N.K.; Prasad R. (My University, 2025)
The analytical solution for unsteady-state temperature distribution in a cylindrical shell with a thin layer of thermal insulation coating on the inner or outer surface is presented. The formula has been derived assuming different initial temperatures of shell and insulation coating and the contact between them has been assumed to be imperfect. The internal and external surfaces of the shell and coating are exposed to non-uniform convective boundary conditions of the third kind. The generalized formula obtained has been used to obtain the warming-up period of the cylindrical wall of a diesel engine coated internally or externally with a ceramic insulation material. A plot of temperature-time history and the heat flow rates have been obtained. The problem considered has application in the transient thermal analysis of an adiabatic engine. Any similar problem in metallurgical, aeronautical, furnace and boiler design applications may be solved by the formula obtained. © 1990.